Investigating the effects of intraoperative fluid management on postoperative outcomes in surgical patients: a prospective cohort study - Sharma, Poorti; Chandrakar, Kunal (Journal of Neonatal Surgery, 2025)
Although fluid therapy is essential to intraoperative anesthesia, there is still much disagreement over the exact kind, quantity, and timing of its administration. Nearly every patient who comes in for general anesthesia will receive some kind of intravenous fluid. Perioperative hydration treatment has been shown to have a significant impact on long-term postoperative results. Recent evidence-based, customized goal-directed treatment (GDT) is challenging the traditional practice of administering huge amounts of crystalloid fluid intraoperatively to every patient. The process of giving fluids during surgery to preserve organ perfusion and blood flow is known as intraoperative fluid management. It entails deciding what kind, how much, and when to administer the fluid. The study evaluates the relationship between intraoperative fluid management and the postoperative outcomes of surgical patients.